Isolated tear of the cord-like middle glenohumeral ligament in Buford complex: A case report. Issue 45 (November 2017) - Lee, Byung-Ill; Kim, Yong Beom; Won, Sung Hun; Hwang, Shu Chiang; Choi, Sung-Woo; Nho, Jae-Hwi; Chun, Dong-il
Abstract: Rationale: We describe a rare case of the isolated tear in the cord-like middle glenohumeral ligament (MGHL) in Buford complex. To the best of our knowledge, this is the first report in the English literature about the isolated tear of cord-like MGHL in Buford complex. The present report describes in detail our experience with the diagnosis of isolated tear of the cord-like MGHL in Buford complex and management. Patient concerns: A 50-year-old female patient visited our hospital with pain and stiffness in the right shoulder that lasted for 9 months. Diagnoses: The clinical impression was frozen shoulder by primary impingement syndrome of right shoulder and the magnetic resonance (MR) images showed tear of cord-like MGHL. Interventions: We repaired the torn MGHL with the arthroscopic technique. Outcomes: Positive outcome by arthroscopic repair demonstrates that this disease entity is one of spectrum of pathologic condition in shoulder joint. Lessons: Isolated tear of cord-like MGHL should be restored to the original anatomy for positive outcome.